Revisiting Reform in the Energy Sector : Lessons from Georgia - Lampietti, Julian A. (Washington, DC: World Bank, 2013)
This paper reviews the changes in the supply of electricity and gas from the perpective of households, utility operators, and the government. The objective is to highlight lessons from the reforms implemented and to apply them to the future reform program planned for the rest of the energy sector. The paper concludes that improved service quality and the increased supply of clean and subsidized natural gas have offset the potentially negative impact of higher electricity prices. Despite very good performance by the privatized electricity distribution company in Tbilisi, the sustainability of the reform program is still in doubt. Consolidated government expenditures on energy have increased, but to a large extent this simply recognizes costs that were incurred, but not paid, prior to reform. Existing subsidies to households for electricity provide compensation beyond levels that produce large welfare gains. Changing the subsidy system to base targeting on actual levels of electricity consumption while providing enough compensation to ensure the household received a basic level of electricity, would be one option to improve subsidy targeting.